2020
DOI: 10.1080/01446193.2020.1818800
|View full text |Cite
|
Sign up to set email alerts
|

The competences of successful safety and health coordinators in construction projects

Abstract: The construction industry is among the most hazardous industries, with a fatality rate in Europe 3.4 times higher than average. While the occupational safety and health (OSH) coordinator has been a key actor in European efforts proposed to improve OSH in the industry since 1992, it is important to study the competences needed for the successful coordination of OSH in the construction industry. Existing literature on OSH coordinator competences are examined, and an expert survey is used to identify the competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There is disagreement in the study as to whether this skill should be modeled as a general capacity or as a subject-specific ability (Jeschke et al, 2021). Møller et al (2020) noted that instructors should explore innovative strategies, such as interactive online activities and case studies, to enhance the application of Knowledge in real-life scenarios during online review sessions.…”
Section: Knowledge Of the Subject Mattermentioning
confidence: 99%
“…There is disagreement in the study as to whether this skill should be modeled as a general capacity or as a subject-specific ability (Jeschke et al, 2021). Møller et al (2020) noted that instructors should explore innovative strategies, such as interactive online activities and case studies, to enhance the application of Knowledge in real-life scenarios during online review sessions.…”
Section: Knowledge Of the Subject Mattermentioning
confidence: 99%
“…Little research has been conducted on the qualifications of safety personnel in the construction industry [11,12]. Møller et al found that several elements shape the desired competencies of a safety coordinator in construction, such as creativity and innovation, being detail-oriented, persistence in implementing proper safety practices, and sociability [17]. Most studies focused primarily on the safety training of construction safety personnel [18] while underestimating the importance of other key qualifications, namely education, experience, and certification of construction safety personnel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experience provides knowledge on safety best practices, rules, and procedures and can also equip safety personnel with a valuable skills kit for managing and mitigating workplace hazards [27]. Experience as the practice of knowing compared to an educational degree for receiving knowledge is a significantly more critical element that defines qualified personnel [17].…”
Section: Experience Of Safety Personnelmentioning
confidence: 99%
“…Accordingly, the safety performance of smaller construction firms is a serious challenge that needs immediate attention through training and education. Reaching smaller firms with OSH interventions across multiple disciplines is challenging [9,10]. The number of small firms is beyond the capacity of most government OSH programs [3].…”
Section: Introductionmentioning
confidence: 99%